EFFECTIVENESS ANALYSIS OF ZAKAT DISTRIBUTION BAZNAS BARRU DISTRICT (International Conference on Social and Islamic Studies, 2022)
This research is motivated by the low realization of zakat distribution in Barru  Regency due to low ratio of the amount of zakat distributed rather than those collected. This study aims to analize the effectively of the zakat distribution. Effectively is realized by targeting accuracy, quality, quantity, monitoring and controlling the distribution of zakat. The research method has been carried out by using qualitative method and descriptive approach. The informant consists of Baznas employee and public figure. The data collection technique has been conducted by using interview and documentary. The data analysis technique has been started by organizing the data, simplifying the data, processing the data analysis, and conclusion drawing. The results showed that Baznas Barru were effectively in targeting accuracy, monitoring and controlling but not yet effective in terms of quality and quantity.